Improving Students' Communication Skills and Understanding of Equivalent Fractions Through Project Based Learning With Toast Maker - Ambawono, Gancar Pramistri; Rahayuningsih, Setiti Rahayuningsih; Siti Inganah (Universitas Nusantara PGRI Kediri, 2025)
This study aims to explore the effectiveness of the Project-Based Learning (PjBL) model in improving students' understanding of equivalent fractions and their communication skills at SD Muhammadiyah 4 Malang. Through the